Pru p 9, a new allergen eliciting respiratory symptoms in subjects sensitized to peach tree pollen - Blanca, Miguel; Victorio Puche, Laura; Garrido-Arandia, María; Martin-Pedraza, Laura; Romero Sahagún, Alejandro; López-Sánchez, José Damian; Galán, Carmen; Marin, Antonio; Villaba, Mayte; Díaz-Perales, Araceli; Somoza, Maria Luisa (PloS one, 2020)
Peach tree (PT) pollen sensitization is highly prevalent in subjects living in areas where this tree is widely cultivated. None of the allergens responsible for these sensitizations have been identified so far. Our aim was to identify the most relevant PT pollen allergens and analyze their capacity for inducing respiratory symptoms. We studied sixty-two individuals sensitized to PT pollen who developed symptoms after its exposure. The IgE binding profile on peach pollen extract by means of immunoblotting using sera from these subjects was analyzed. Protein extract was fractionated by anion-exchange chromatography and HPLC, fractions run in SDS-PAGE and proteins were identified from IgE-binding bands by mass spectrometry. Several allergenic proteins in the PT pollen extract were recognized by patients' IgE: a glucan endo-1,3-beta-glucosidase-like, a polygalacturonase, an UTP-glucose-1-phosphate uridylyltransferase and a PR-1a protein. This PR-1a protein is a novel allergen frequently recognized with a molecular mass of 18 kDa, named as Pru p 9 following the WHO-IUIS nomenclature. Skin Prick Test (SPT) performed with this allergen was positive in 41% of the PT pollen-sensitized clinical cases. Most of them had rhinitis or rhinoconjunctivitis, but a significant percentage experienced asthma with seasonal symptoms during the period of PT flowering. Nasal Provocation test (NPT) with Pru p 9 was positive in all cases with positive SPT to this new allergen eliciting nasal symptoms similar to those challenged with PT pollen. We demonstrate that PT pollen can induce sensitization and allergy in an exposed population, being Pru p 9 a relevant allergen responsible of respiratory symptoms. Considering the extensive peach worldwide production with a large number of people involved, our results add a great value for the diagnosis and management of subjects allergic to this pollen.